Estimating Market Potential for Solar Photovoltaic Systems in Uganda - Aarakit, Sylvia Manjeri; Ssennono, Vincent Fred; Adaramola, Muyiwa S. (Frontiers in Energy Research, 2021)
With only 28% of the population having access to electricity, Uganda presents a huge market potential for alternative technologies to provide electricity such as solar PV systems. Using a simple statistical method (neighbourhood approach), this study estimates the market potential for solar PV in households based on a 2018 National Electrification Survey dataset collected by Uganda Bureau of Statistics (UBOS). Results show that approximately 5.3 million households lack access to electricity, thus the total market potential. Over 60% of households lack access to electricity due to supply-side gaps (also known as absence of coverage) while the rest of the households have coverage but lack access due to demand side limitations (also known as no uptake). On the contrary, our results suggest that supply-side gaps constitute the biggest proportion of electricity access deficit in Uganda’s households. Implying that these households may be willing and have the ability to pay but lack supply, thus these households constitute an immediate market potential for solar PV systems. To address the electricity access deficit, private solar companies should target unserved households with appropriate systems/products and innovative business models to suit their needs. Government on the other hand should subsidize households with affordability challenges or enhance their income.